Hukum Tata Negara tentang Pemerintah dan Otonomi Daerah - Fitriani, Hellen Last; Nurhadi, Nurhadi (YASIN, 2022)
State Philosophy Officially explaining the 1945 Constitution, in general, regarding the main idea in the preamble of the 1945 Constitution, it is said that "a state that has sovereignty over the people based on democracy and deliberation of representatives". So the state will not run well without regional or autonomous administrators. Therefore, it is necessary to know what local government is, the principles, the relationship between the center and the regions, authority, council representation, systematics for forming regional and autonomous governments? Furthermore, it can be explained that according to Law Number 23 of 2014 concerning Regional Government, regional government is the implementation of government affairs by regional governments and the Regional People's Representative Council (DPRD) using the principle of autonomy and co-administration with the principle of autonomy as wide as possible in the system and principles of the State. The Unity of the Republic of Indonesia as referred to in the 1945 Constitution of the Republic of Indonesia. The relationship between the central and local governments by Clarke and Stewart is conceptualized in three forms, namely: The Relative Autonomy Model, The Agency Model and The Interaction Model. Local government powers include: Externalities; Accountability and Efficiency. The legislation in question includes: (i) Law no. 18 of 1965 concerning the Principles of Regional Government (hereinafter referred to as Law 18/1965), (ii) Law no. 5 of 1974 concerning the Principles of Regional Government (hereinafter referred to as Law 5/1974), (iii) Law no. 22 of 1999 concerning Regional Government (hereinafter referred to as Law 22/1999), (iv) Law no. 32 of 2004 concerning Regional Government (hereinafter referred to as Law 32/2004), (v) PERPPU No. 3 of 2005 concerning Amendments to Law no. 32 of 2004 concerning Regional Government (hereinafter referred to as PERPPU 3/2005), (vi) Law no. 8 of 2005 concerning Stipulation as Law on PERPPU No. 3 of 2005 concerning Amendments to Law no. 32 of 2004 concerning Regional Government (hereinafter referred to as Law 8/2005), and (vii) Law no. 12 of 2008 concerning the Second Amendment to Law no. 32 of 2004 concerning Regional Government (hereinafter referred to as Law 12/2008). . In the general explanation of Law Number 32 of 2004 it is stated that the formation of regions is basically intended to improve public services in order to accelerate the realization of community welfare as well as as a means of political education at the local level.